Analysis of the interface stress of riser composite piles. (3rd March 2023) - Cai, Runbo; Liang, Chao; Yang, Xu; Wan, Jun; Yu, Jiandong
ABSTRACT: The finite element method was used to analyse the interface stress of composite piles under vertical, horizontal and temperature loads. The results show that under vertical load, the cementing cement of composite piles has stress concentration at the position where section varied, and when the settlement of the pile top exceeds 150 mm, the cement has the risk of crushing. Under horizontal load, a tensile crack area appears on the tensile side of the cement, and the length of the tensile fracture area increases with the increase of the displacement of the pile top. Under temperature load, the maximum interface shear stress increases with the increase of temperature. Under the action of vertical, horizontal and temperature loads, the shear stress between each material of the pile is less than the bonding strength of the material, and the bonding surface will not slide relative to each other.